Power and Urban Planning: Genesis and Critical Analysis of Theoretical Approaches - Slavkovic, Ljubica (Arhitektura i urbanizam, 2025)
Urban planning has traditionally been dominated by rationalist and technocratic paradigms, within which the question of political power has often been treated as peripheral. With the rise of critical social theories in the second half of the twentieth century, planning increasingly came to be understood as a politically embedded process, where relations of power play a central role in shaping space and public policy. However, under the contemporary neoliberal paradigm, the planning arena once again tends to be “depoliticized.” This paper critically examines how the concept of power has been articulated and transformed across three key theoretical frameworks: the rationalist–technocratic model, the communicative approach (grounded in Habermas’s conception of the public sphere), and the Foucauldian discourse perspective. The analysis engages with influential authors and concepts, including Harvey, Lefebvre, Healey, Forester, and Flyvbjerg, and seeks to identify paradigmatic shifts and the implications that differing understandings of power have produced in planning theory and practice. The paper highlights the need for an analytical framework capable of bridging the gap between normative theorizing and the empirical configurations of power that shape contemporary urban governance.